2022
DOI: 10.1097/md.0000000000029133
|View full text |Cite
|
Sign up to set email alerts
|

Supporting business educators and students against COVID-19 trauma using trauma-focused cognitive behavioral therapy

Abstract: Background:The outbreak of COVID-19 manifests in peoples’ mental health and psychological dispositions and may also result to acute distress, depression, anxiety and post-traumatic stress disorder (PTSD) on victims. The objective of this study was to support business educators’ and students’ mental health against coronavirus trauma using trauma-focused cognitive behavioral therapy (TF-CBT).Methods:The participants (n = 74 – educators and students) who indicated PTSD symptoms based on the self-reporting questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Further, the study also found that age also had no association with the emergence of post-traumatic anxiety symptoms experienced by individuals. Edeh et al (2022) also described no significant difference in the traumatic effects after the COVID-19 pandemic between individuals of a different gender. In a study conducted to find out the growing symptoms of post-traumatic anxiety in adolescents after the COVID-19 pandemic, Zhang et al (2021) also found similar results.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Further, the study also found that age also had no association with the emergence of post-traumatic anxiety symptoms experienced by individuals. Edeh et al (2022) also described no significant difference in the traumatic effects after the COVID-19 pandemic between individuals of a different gender. In a study conducted to find out the growing symptoms of post-traumatic anxiety in adolescents after the COVID-19 pandemic, Zhang et al (2021) also found similar results.…”
Section: Discussionmentioning
confidence: 93%
“…Accordingly, schools need to pay close attention to students' mental health in order to aid them in avoiding PTSD, since PTSD will hinder their development. As an alternative, schools need to provide facilities for enhancing students' independence (Edeh et al, 2022). The preventive and curative alternatives should also be carried out to prevent PTSD as well as lowering the PTSD symptoms experienced by students.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, essential measures should also be taken on medium-level maintaining groups to change into an escalating group. Trauma-focused-cognitive behavior therapy (TF-CBT) was widely evidenced as a recommended psychological intervention for its both short-term and longterm efficacy on post-traumatic stress disorder (PTSD) in youth (33,34), which may be helpful to build resilience and improve the individuals' initial traumatized conditions. In addition, for the rapid development of digital health interventions and digital platforms, it is essential to incorporate psychological support for college students through listening and counseling services with the implementation of digital psychological interventions to contain, as far as possible, the evolution and structuring of psychopathological profiles during traumatic events (2).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the lecturers in the Departments of Educational Foundation and Business Education are faced with series of academic stressors due to so many social, environmental, and behaviourial factors from the academic milieu. [ 16 ] Some of the stressors stem from their core academic activities such as development of course materials, planning lessons, and organizing of academic curricula. They also experience stress through the setting of quizzes and examinations and grading them as well as supervision of the students’ projects and theses.…”
Section: Introductionmentioning
confidence: 99%
“…All these stressors influence both their reasoning, and relationship with people. [ 16 ] There is agreement among the authors that the teaching profession is a very stressful career because of heightened psychosocial stressors at the workplace. [ 17 ] For instance, Oshineye et al [ 17 ] found that lecturers are always engrossed with volumes of work which extract a lot of energies out of them and put pressures on their health.…”
Section: Introductionmentioning
confidence: 99%